Osteopontin Impacts West Nile virus Pathogenesis and Resistance by Regulating Inflammasome Components and Cell Death in the Central Nervous System at Early Time Points - Nikki Bortell; Claudia Flynn; Bruno Conti; Howard S. Fox; Maria Cecilia G. Marcondes (Mediators of Inflammation)
Osteopontin (OPN) is a molecule that is common in central nervous system (CNS) pathologies, which participates in the activation, migration, and survival of inflammatory cells. However, the mechanisms by which OPN modulates inflammatory pathways are not clear. To understand the role of OPN in CNS viral infections, we used a lethal mouse model of West Nile virus (WNV), characterized by the injection of high doses of the Eg101 strain of WNV, causing the increase of OPN levels in the brain since early time points. To measure the impact of OPN in neuropathogenesis and resistance, we compared C57BI/6 WT with mice lacking the OPN gene (OPN KO). OPN KO presented a significantly higher mortality compared to WT mice, detectable since day 5 pi. Our data suggests that OPN expression at early time points may provide protection against viral spread in the CNS by negatively controlling the type I IFN-sensitive, caspase 1-dependent inflammasome, while promoting an alternative caspase 8-associated pathway, to control the apoptosis of infected cells during WNV infection in the CNS. Overall, we conclude that the expression of OPN maintains a critical threshold in the innate immune response that controls apoptosis and lethal viral spread in early CNS infection.